Finnish agrifood sector outlook 2023 - Latvala, Terhi; Väre, Minna; Niemi, Jyrki (Natural Resources Institute Finland, 2023)
Economic growth in Finland remains weak Uncertainty about international economic development and its impact on Finland remains high. The start of 2023 has been marked by persistently weak business and consumer confidence. However, the recovery of consumers’ purchasing power is supported by lower inflationary pressures at the end of the year and an increase in wages. The Finnish economy is expected to contract by 0–0.5% in 2023. The increase in food prices is expected to decelerate In 2022, there were unusual pressures to increase food prices, as the prices of the production inputs in the food chain increased significantly. Food prices increased by an average of 10.5% in 2022, while there were significant differences in the development of the prices of various food products. The prices continued to increase steeply at the beginning of 2023, and there will be cost pressures on food prices with a delay. The price increase is expected, however, to decelerate during 2023. The trade deficit of all plant- and animalbased products increased The export value of all animal- and plant-based products from Finland increased significantly in 2022 compared to previous years – due to the steep increase in the prices of agricultural products and foodstuffs. The value of exports reached EUR 2,199 million, up by 23.1% from the year before. The value of animal- and plant-based products imported into Finland was EUR 6,817 million, roughly 23.4% more than in the previous year. The trade deficit of all plant- and animal-based products increased by EUR 879 million – from EUR 3,739 to EUR 4,618 million – marking the largest annual change in history. Agricultural policy requires more environmental and climate measures The new term of the EU agricultural policy started at the beginning of 2023. Total EU funding for Finnish agriculture will remain close to the previous level. However, reaching the previous support level requires more action from farmers regarding the environment and climate measures. The basic mandatory requirements to obtain direct support financed wholly or partly by the EU, will be stricter than before. Eco-schemes for direct support will be introduced as a completely new element, which are voluntary actions selected annually by farmers. The grain market has calmed down The high yields of 2022 stabilised the cereals market. Finland also strengthened the stocks of bread cereals after the shortage in spring 2022. Based on preliminary data about cultivated areas for 2023, lower cereal yields are expected, roughly 3.2 million tons, while the final volume may deviate by more than 10% in either direction as a result of growth conditions. The final harvest level will have an impact on prices in Finland, even though the price level is largely determined according to European and, more broadly, global supply and demand situation. Cultivation of oil and protein crops increased In 2022, the production volumes of oilseed and protein crops grew driven by increased surface areas and high average yields. Self-suffciency in complementary proteins increased significantly from the previous years’ level to almost 27%. However, yields in 2023 are expected fall behind the previous years’ levels if the weather conditions remain normal which would return this year’s self-suffciency rate to a lower level. Meat consumption and production are decreasing Higher costs and the resulting increases in producer and consumer prices have caused significant changes in the Finnish meat markets. The financial situation has improved on meat farms, while differences between farms have increased. The production and consumption of meat fell in 2022, and both are expected to decrease further in 2023. In 2022, pork saw the largest decrease in production and beef in consumption. As a result of these changes, the self-suffciency rate will decrease in pork and increase in beef. Overall, the focus of the consumption structure is shifting to more affordable product groups. The economic situation of milk production has fluctuated The dairy sector experienced a highly exceptional year in economic terms in 2022. The cost crisis that started in the previous year continued, while the unusual increase in producer prices that started at the beginning of the year eventually slowed the steep decline in profit margins. The stabilisation of feed costs at the end of the year, supported by the relatively large cereal harvest, enabled the profit margin of milk to return to the average level of the previous years. However, milk producer prices have already started to fall from their peak levels in Europe, and Finland will also see a return close to the recent years’ situation in 2023. Producer price of eggs increased by almost 28%, organic sales decreased In 2022, egg consumption decreased by 5.3% and egg production by 1.6% from the previous year. Both consumption and production are expected to remain roughly at the same level in 2023. The consumer prices of eggs increased last year, being as much as a quarter (25%) higher than in the previous year on average. The producer price of all eggs grew by roughly a third (28%). A significant drop was seen in sales of organic eggs, whose market share was 16% of total consumption measured by value. Horticultural production is concentrating strongly In recent years, the number of horticultural enterprises has decreased, even though production has remained unchanged or even increased. The concentration of production in specific areas and on large farms has accelerated. The ten largest producers cover already 82% of Finland’s total cucumber production. For tomatoes, the corresponding figure is 56%. The aging of farmers affects the development of agriculture The number of farms is decreasing, and the average farm size continues to increase. In 2022, the total number of agricultural and horticultural enterprises was 43,611. As there are fewer farm successions, the averageage of farmers is increasing, and more and more farms will be run byfarmers of retirement age. During the next ten years, a third of Finland’sfarmers will reach retirement age. This will also inevitably have an impacton the development of agriculture. Price fluctuations affected the farms’ finances The price turbulence in 2022 had a significant impact on the economy of farms. According to estimates, profitability in agriculture in 2022 was almost as low as in the previous year. Costs on farms first increased steeply, while producer price increases followed with a delay. Cost pressures were especially reflected in the low profitability of livestock farming. The profitability of cereal and oilseed and protein crop farming improved from the previous year.
Keywords: agriculture and food markets; agricultural policy; food production; food consumption and prices; agricultural structures